3 Fakta Menarik Tentang Kedudukan dan Peran Pendidikan Islam dalam Sistem Pendidikan Nasional - Pulungan, Muhammad Rezki; Adisel, Adisel; Nuryanti, Nuryanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this research is to know what are the roles and positions of Islamic Education in National Education. This type of research is library research. The data collection of this research was taken from primary and secondary data sources. The results of the study, that the role and position of Islamic education in national education, namely: 1) Religious education is held by the government and community groups of religious adherents, in accordance with statutory regulations. 2) Religious education serves to prepare students to become members of the community who understand and practice the values ​​of their religious teachings and/or become experts in religious knowledge. 3) Religious education can be held in formal, informal and non-formal education channels. Religious education is in the form of diniyah education, pesantren, pasraman, pabhaja samanera and other similar forms. In conclusion, the position of Islamic education in the national education system is flexible, sometimes as a subject and sometimes as an institution (educational unit). Religious education as a source of values ​​and part of national education. Religious education has an urgent role in developing the potential of students to have religious spiritual strength, noble character and Muslim personality (specifically Islam). Keywords: Position of Islamic Education, National Education System.